Ring-opening cyclization of spirocyclopropanes with stabilized sulfonium ylides for the construction of a chromane skeleton. Issue 46 (20th May 2019) - Nambu, Hisanori; Onuki, Yuta; Ono, Naoki; Tsuge, Kiyoshi; Yakura, Takayuki
Abstract : A regioselective ring-opening cyclization of spirocyclopropanes with sulfonium ylides afforded 2, 3- trans -hexahydrobenzopyran-5-ones in high yields without the formation of any diastereoisomers. Abstract : Regioselective ring-opening cyclization of cyclohexane-1, 3-dione-2-spirocyclopropanes with stabilized sulfonium ylides provided 2, 3- trans -disubstituted 2, 3, 4, 6, 7, 8-hexahydro-5 H -1-benzopyran-5-ones in high yields without the formation of any isomers. The obtained product was readily converted into highly substituted chromane.